Pediatric Acute Respiratory Distress Syndrome and Sepsis in Children with Dravet Syndrome Following Upper Respiratory Tract Infections - Schwarz, Friederike; Oesch, Gabriela; Aebi, Christoph; Kieninger, Elisabeth; Riedel, Thomas (Archives of Clinical and Medical Case Reports, 2024)
Herein we report on four children with SCN1A related Dravet syndrome (DS) with severe pediatric acute respiratory distress syndrome (PARDS) and sepsis following upper respiratory infections that have occurred in clusters over a short period of time. Complications included PARDS with need of veno-venous extracorporeal membrane oxygenation (VV-ECMO) and acute kidney injury treated with continuous veno-venous hemodiafiltration (CVVHDF). This striking observations warrant further exploration of DS patients’ susceptibility to respiratory tract infections.